The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1432-1033.1994.tb18855.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐phase synthesis, conformational analysis and in vitro cleavage of synthetic human synaptobrevin II 1–93 by tetanus toxin L chain

Abstract: A 93-residue peptide corresponding to the cytosolic domain of a human vesicle associated membrane protein (VAMP or synaptobrevin) has been prepared by solid-phase peptide synthesis in order to investigate the proteolytic activity of the tetanus toxin light chain (TeTx L chain). This protein has been recently reported to inactivate the neuronal rat synaptobrevin I1 by proteolysis. We show in this study that the synthetic human synaptobrevin I1 1-93 (Syb I1 1-93) as well as an Nterminus-shortened 69-residue pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 46 publications
3
27
0
1
Order By: Relevance
“…Likewise, Snc2p appears to be unfolded as judged by CD spectroscopy (Fig. 2a) and amide proton exchange experiments (data not shown), in accord with previous reports for Snc2p homologs 26,33 . Unlike Sso1p and Sso2p, which display CD spectra indicative of substantial (~70%; see Methods) α-helix content, Sso1CT and Sso2CT are largely unfolded (Fig.…”
Section: Assembly-induced Folding Of Snare Domainssupporting
confidence: 90%
“…Likewise, Snc2p appears to be unfolded as judged by CD spectroscopy (Fig. 2a) and amide proton exchange experiments (data not shown), in accord with previous reports for Snc2p homologs 26,33 . Unlike Sso1p and Sso2p, which display CD spectra indicative of substantial (~70%; see Methods) α-helix content, Sso1CT and Sso2CT are largely unfolded (Fig.…”
Section: Assembly-induced Folding Of Snare Domainssupporting
confidence: 90%
“…Indeed, the formation of a unique tertiary structure, comparable to that of S 27-93, by mixing the three short peptides S 27-55 (S 1 ), S 56 -81, and S 82-93 (S 2 ) is highly improbable. This is supported by the lack of a well defined tertiary structure for synaptobrevin in solution as previously observed by 1 H NMR (29). A mechanism which could account for the present results is the promotion of an active conformation of TeNT induced by the binding of the S 1 and S 2 domains of synaptobrevin to exosites present on the toxin surface, as in the case of allosteric enzymes (36 -38).…”
Section: Discussionsupporting
confidence: 71%
“…TeNT cleaves synaptobrevin selectively at one single peptide bond Gln 76 -Phe 77 (28). Successive truncations of synaptobrevin at its NH 2 and COOH terminus have shown that the removal of both the proline-rich NH 2 -terminal 1-25 domain and the 93-116 transmembrane anchor does not reduce the rate of hydrolysis by TeNT (29,30) (Fig. 1).…”
mentioning
confidence: 99%
“…The ability of this latter toxin to inhibit TeNT and BoNT/B proteolysis of VAMP, documented in Fig. 3b, was reduced when VAMP-2 D64S,D65S mutant and the VAMP-2 Asp 40 and Glu 41 were assayed (not shown). However, results did not allow us to draw a clear conclusion of a possible preference of BoNT/A between V1 and V2.…”
Section: Mutation Of the Negatively Charged Residues Of V1 Affects Vamentioning
confidence: 91%